1993
DOI: 10.1063/1.352785
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the electrical resistivity of reactively sputtered TiN films

Abstract: The electrical resistivity of reactively sputtered TiN films was measured as a function of film thickness. The effect of directionality of the sputtered atoms, substrate temperature, bias voltage, deposition rate, and film morphology on the electron conductivity in TiN films was studied. The combination of rapid deposition rate and high substrate temperature with bias-collimated sputtering results in TiN films with the lowest resistivity, 45 μΩ cm, the largest temperature coefficient of resistance, 1355 ppm, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 28 publications
5
16
0
Order By: Relevance
“…Bulk TiN material is a superconductor with a transition temperature below 6 K. 1 Experiments have demonstrated that the critical temperature of thin TiN films decreases with decreasing thickness, i.e., with increase of the sheet resistance (in the normal state). 2,3 Furthermore, the critical temperature of the TiN films can be controlled over a wide range (0 < T c < 5 K) by varying the N 2 concentration during the deposition. 1,4,5 The superconducting transitions remain sharp over the whole range of T c values.…”
mentioning
confidence: 99%
“…Bulk TiN material is a superconductor with a transition temperature below 6 K. 1 Experiments have demonstrated that the critical temperature of thin TiN films decreases with decreasing thickness, i.e., with increase of the sheet resistance (in the normal state). 2,3 Furthermore, the critical temperature of the TiN films can be controlled over a wide range (0 < T c < 5 K) by varying the N 2 concentration during the deposition. 1,4,5 The superconducting transitions remain sharp over the whole range of T c values.…”
mentioning
confidence: 99%
“…In single-crystalline TiN the electrical resistivity at room temperature is 18 µΩ cm [55]. Resistivities of polycrystalline films are typ- ically in the range of 25-1000 µΩ cm [75,[83][84][85]. Such an increase in resistivity from a single-crystal to a polycrystalline film is due to scattering from the grain boundaries, vacancies and possibly also oxynitrides associated with the polycrystalline TiN [83,86].…”
Section: Electronic and Optical Propertiesmentioning
confidence: 94%
“…Thin-film nitride structures are widely used in microelectronics and other technological applications as barrier layers in multilevel contact systems of integrated circuits; surface-hardening, corrosion-resistant, and decorative coatings; and thermistor materials [1][2][3][4][5][6][7][8][9][10][11][12]. Potential applications of thin-film materials in solidstate electronics depend on their temperature-dependent resistivity and thermoelectric power [13].…”
Section: Introductionmentioning
confidence: 99%
“…The electrical and thermoelectric properties of reactively sputtered films (primarily TiN films) were described in many reports [2,4,5,[7][8][9][10][11][12]. At the same time, little or no data exists on the properties of films produced by ion implantation, the most effective approach to improving the physicochemical properties of materials [14,15].…”
Section: Introductionmentioning
confidence: 99%